2020
DOI: 10.1111/tbed.13805
|View full text |Cite
|
Sign up to set email alerts
|

Formal estimation of the seropositivity cut‐off of the hemagglutination inhibition assay in field diagnosis of influenza D virus in cattle and estimation of the associated true prevalence in Morocco

Abstract: The influenza D virus (IDV) was discovered less than ten years ago. Increased interest in this virus is due to its nature (RNA virus with high mutation rate), its worldwide circulation in livestock species, its probable role in bovine respiratory disease and its zoonotic potential. Until currently, the establishment of positivity cutoff of the hemagglutination inhibition (HI) assay was not formalized in field conditions for the detection of antibodies directed against IDV in cattle (i.e. the proposed reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The HI titer was expressed as the reciprocal of the highest serum dilution showing complete inhibition of hemagglutination. A serum sample was determined as seropositive when the HI titer was ≥1: 10 [ 11 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The HI titer was expressed as the reciprocal of the highest serum dilution showing complete inhibition of hemagglutination. A serum sample was determined as seropositive when the HI titer was ≥1: 10 [ 11 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies around the globe have reported the circulation of IDV in either healthy or sick cattle, small ruminants and swine from China, France and the USA [30,32,34,117,118]. This review and meta-analysis demonstrated the presence of IDV specific antibodies in cattle from Benin, Morocco and Togo [40,90,91], camels from Ethiopia and Kenya [40,92] and small ruminants from Ethiopia and Togo [40,91,92]. However, no viral RNA of IDV was detected, possibly due to the absence of active infection in the animals during the period of sampling, the limited number of samples collected in each study, and the limited number of studies conducted in Africa.…”
Section: Discussionmentioning
confidence: 76%
“…Exposure to IDV was reported in East Africa, North Africa and West Africa. IDV antibodies were detected in cattle from Benin [40], Morocco [90] and Togo [40,91], in dromedary camels from Kenya [40] and Ethiopia [92], and in small ruminants from Ethiopia and Togo (Table 2). Further, the review of the literature suggests that IDV has been circulating in Africa since 2012 as evidenced by the antibodies detected in Morocco [40].…”
Section: Distribution Of Influenza a And D Viruses And Detection Of Antibodies In Non-human Mammalian Hosts In Africamentioning
confidence: 99%
“…Nevertheless, a proper estimation of relative importance of illegal movements of live animals and their introduction pathways is deemed essential to set up risk-based awareness, prevention and surveillance programmes that correspond to reality. While direct (isolation of the virus and real-time polymerase chain reaction) Ferguson et al, 2015;Hause et al, 2013) and indirect (seroneutralization, haemagglutination inhibition assays and monoclonal antibody-based competitive ELISA) (Moreno et al, 2018;Saegerman, Salem, et al, 2020) diagnostic tests have been set up for IDV, the absence of commercial assays limits the possibility to implement a proper testing strategy in order to control the trade of live animals and to certify the sanitary IDV status of the herd of origin.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth most important driver was the vaccine availability (D3-2). The worldwide spread and inter-species transmission of IDV could be prevented and controlled either thanks to an effective vaccine, or thanks to antiviral strategies (Asha & Kumar, 2019;Saegerman, Salem, et al, 2020). The use of antivirals in animals is not advised due to high treatment costs and risk of emergence and spread of resistant influenza strains (Kesinger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%